Experience of skill labs to improve quality of newborn care at birth in three district of Uttar Pradesh, India - Das, Manoja Kumar; Chaudhary, Chetna; Kaushal, Santosh Kumar; Khanna, Rajesh; Chatterji, Surojit (International Journal Of Community Medicine And Public Health, 2017)
Background: Retention of neonatal resuscitation skill among birth attendants have been a challenge in developing countries. The objective of the study was to document the performance of skill labs and its impact on the skill and knowledge of the birth attendants in India. Methods: In three districts of Uttar Pradesh, impact assessment of twelve skill labs was done adopting mixed quantitative and qualitative methodology. Results: Twelve skill labs supported skill building of 606 birth attendants over one year. Six of the units performed well and four moderately and too units poorly. The health functionaries at all levels were positive about their experience about the skill labs. Majority of them hoped sustenance of these units. There was marked retention of resuscitation skill after one year. Conclusions: The skill labs appear to be useful modality for promoting retention of the resuscitation skills of birth attendants.